Description of Pseudoschoengastia petrolinensis n. sp. (Trombidiformes: Trombiculidae), and new records of chiggers from northeastern Brazil - Jacinavicius, Fernando de Castro; Bassini-Silva, Ricardo; de Oliveira, Glauber Meneses Barboza; Horta, Maurício Claudio; Welbourn, Cal; Ochoa, Ron; Barros-Battesti, Darci Moraes [UNESP] (Taylor & Francis, 2019)
The species Pseudoschoengastia petrolinensis n. sp. is described and illustrated below from specimens discovered parasitizing a white-eared opossum, Dildelphis albiventris Lund (Didelphimorphia, Didelphidae), in Carneiros, Petrolina municipality, Pernambuco state, Brazil. In addition the species Eutrombicula spipi and Quadraseta falconensis are also new records to Brazil. The D. albiventris is a new host record to Eutrombicula batatas, E. spipi, Q. falconensis, and the state of Pernambuco is a new locality for all these species. http://www.zoobank.org/urn:lsid:zoobank.org:pub:97650D6C-A920-402C-BA90-78B2AB9B6187.
Keywords: didelphimorphia; ectoparasites; mammals; Mites; pernambuco state